(untitled) (Bangladesh Journal of Zoology, 2018)
Cinnamon has different biological properties such as antioxidant, antimicrobial, antidiabetic and antiallergic. This study was carried out to investigate the effect of cinnamon as feed supplement on growth performances and bacterial load of Heteropneustes fossilis. Twenty fries were stocked in each 60 litre aquarium for a rearing period of 90 days. Commercial diet was used that contains 0.0% (control), 0.5%, and 1.0% cinnamon bark powder. The diet containing 1% cinnamon resulted in greater ADG, SGR, FCR and survival rate. Whereas, the diet containing 0.5% cinnamon resulted in greater condition factor and lower FCR. In most of the cases the diet containing 1% cinnamon showed lower amount of bacterial count than the controlled condition. Cinnamon could have an antibacterial activity antagonistic to Vibrio and Aeromonas as there was no count found in fish flesh samples after 90 days of culture. The findings of this study suggest that growth performances and bacterial load of H. fossilis were better in commercial feed containing cinnamon powder. It is recommended that fish farmers can use cinnamon as feed supplement to improve growth performance and reduce bacterial load during culture of H. fossilis. Bangladesh J. Zool. 46(2): 155-166, 2018